F Formulasi dan Antibakteri Sediaan Sabun Cair Ekstrak Daun Sembung (Blumea Balsamifera) terhadap bakteri Staphylococcus aureus: Formulasi dan Evaluasi - Romadhina, Rodhiatul; Budi, Setia; Rohama, Rohama (LPPM Universitas Sari Mulia, 2023)
Background: The skin is a part that is susceptible to exposure to chemical, physical substances as well as bacteria, fungi and viruses. The bacteria that is often found on the skin is Staphylococcus aureus. To overcome this, soap making needs to be done, one of which uses sembung leaf extract which has biological activity as antibacterial. Objective: Extracting sembung leaves and making formulations of antibacterial liquid soap preparations of sembung leaf extracts and analyzing antibacterial preparations of liquid soap preparations of sembung leaf extracts Methods: The research method method used is experimental with true experimental design and the research design uses post test only with control group design. Making 3 kinds of antibacterial liquid soap formulations sembung leaf extract with concentrations of 5%, 7%, and 10%. Then evaluation includes pH, organoleptic, high foam, viscosity, and antibacterial test. Results: Based on the results of the organileptic test, there was no difference between each formulation of liquid soap extract from Sembung (Blumea balsamifera) leaf extract. Then in the pH test, it is included in the vulnerable pH of liquid soap, namely pH 8-11. After that, in the foam height test, the results of the foam height test were included in the foam height test vulnerable, namely 13-220 mm. Then, the viscosity test results obtained that the viscosity test is included in the viscosity test vulnerability, namely 400-4000 cPs. Finally, the anti-bacterial test obtained clear results of the diameter of the inhibition zone in each formulation. Conclusion: All formulations meet the SNI standard for liquid soap for pH testing, organoleptic testing, high foam testing, and viscosity testing. In antibacterial testing against Staphylococcus aureus bacteria using the disc method the best formula was obtained, namely a concentration of 5%.